1960
DOI: 10.1071/ar9600257
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of estimates of repeatability and heritability for some production traits in Merino rams and ewes. I. Repeatability

Abstract: Repeatabilities of 10 traits, namely, greasy wool weight, clean scoured yield, clean wool weight, body weight, wrinkle score, face cover score, fibre population density, fibre diameter, staple length, and crimps per inch, were estimated in ewes and rams. Estimates ranged from 0.4 to 0.7 for the 10 traits in both sexes. In general, body weight was the most repeatable trait and face cover the least. There is no evidence of sex differences in repeatability of the traits studied. Correlations between pairs of reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
2

Year Published

1964
1964
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
4
8
2
Order By: Relevance
“…The high genetic correlations between the two age expressions of each trait, and between BDWR and NKWR, indicate that the same genes are controlling the expression of these traits at both the yearling and adult stage of assessment which is in agreement with earlier studies across a wide range of Merino genotypes and environments (Beattie, 1962;Jackson and James, 1970;Mortimer and Atkins, 1993;Lewer et al, 1995;Robinson et al, 2007;Mortimer et al, 2009;Scholtz et al, 2010). Previous research indicates that BDWR and NKWR are highly repeatable (Young et al, 1960;Beattie, 1961;Hatcher et al, 2009) across a range of superfine to broad wool Merino types which implies that a single measure of either trait would be sufficient to include in a breeding program for plainerbodied sheep.…”
Section: Neck and Body Wrinkle Traitssupporting
confidence: 78%
“…The high genetic correlations between the two age expressions of each trait, and between BDWR and NKWR, indicate that the same genes are controlling the expression of these traits at both the yearling and adult stage of assessment which is in agreement with earlier studies across a wide range of Merino genotypes and environments (Beattie, 1962;Jackson and James, 1970;Mortimer and Atkins, 1993;Lewer et al, 1995;Robinson et al, 2007;Mortimer et al, 2009;Scholtz et al, 2010). Previous research indicates that BDWR and NKWR are highly repeatable (Young et al, 1960;Beattie, 1961;Hatcher et al, 2009) across a range of superfine to broad wool Merino types which implies that a single measure of either trait would be sufficient to include in a breeding program for plainerbodied sheep.…”
Section: Neck and Body Wrinkle Traitssupporting
confidence: 78%
“…The estimates of repeatability of NL W found in this study are not dissimilar to those reported by Young et al (1963), Purser (1965), Inskeep et al (1967), and Kennedy (1967) although the range of 0.12-0.25 published by Rae & Ch'ang (1955) is higher than that in Table 2.…”
Section: Number Of Lambs Weanedcontrasting
confidence: 52%
“…It can be concluded from the accumulated evidence that FW is highly repeatable. Wright & Stevens (1953) and Young et al (1960) also observed that more widely spaced records are less repeatable than adjacent records.…”
Section: Greasy Fleece Weightmentioning
confidence: 99%
See 2 more Smart Citations